Fasting Intervention for Children With Unilateral Renal Tumors to Reduce Toxicity - Oudmaijer, Christiaan A. J.; Boogaard, Winnie M. C. van den; Komninos, Daphne S. J.; Verwaaijen, Emma J.; Santen, Hanneke M. van; Lilien, Marc R.; Hoeijmakers, Jan H. J.; Wijnen, Marc H. W.; Heuvel-Eibrink, Marry M. van den; Vermeij, Wilbert P. (Frontiers in Pediatrics, 2022)
Childhood renal tumours account for around 6% of all childhood cancers and 90% of these cases are Wilms tumour. In Europe, the SIOP-RTSG approach is considered standard of care and has resulted in five-year survival rates of over 90%. Efforts to decrease toxicity are now being pursued. Short-term fasting (STF), a short but strong reduction in calorie-intake, is associated with improved fitness, enhanced coping with acute physical stress and a lower risk of age-associated diseases. STF temporarily reduces growth to boost resilience, maintenance, and defence-mechanisms, by which toxic side-effects of (oxidative) damage and inflammation are largely prevented. Renal surgery for Wilms tumour carries a risk of acute kidney injury (AKI) and paediatric patients that had an episode of AKI are at increased risk for developing chronic renal disease. STF could mitigate surgery-induced stress and could further improve outcomes. We aim to investigate the effect of STF on renal function recovery after renal tumour surgery by conducting a single-centre, prospective, randomized, non-blinded, intervention study. Children diagnosed with a unilateral renal tumour and opting for curative treatment are eligible for inclusion. The main study objective is to investigate the potential decrease in occurrence of AKI due to STF. Secondary objectives include renal function recovery, child’s wellbeing, physical functioning, and feasibility of and adherence to STF in children with cancer.